Design of a Web-Based Self-Reporting Information System for Teacher Professional Education - Fatih Dwi Laksana; Rizki Suwanda (Politeknik Ganesha Medan, 2024)
The manual self-reporting process for students in the Teacher Professional Education (PPG) program leads to delays, data inaccuracies, and administrative complexities. This research focuses on personal information of PPG students, educational history, and assignment documents. Data collection methods included interviews, observations, and document studies. The system development method followed the waterfall approach, involving requirements analysis, system design, implementation using PHP as the primary programming language, testing, and evaluation. The resulting information system leverages web technology and PHP to facilitate self-reporting for PPG students. Key features include online reporting forms, student data management, and handling PPG-related documents. Evaluation results indicate improved efficiency, accuracy, and speed in administrative processes, along with increased student engagement in self-reporting. The conclusion of this research is that the implementation of the web-based PPG Self-Reporting Information System using PHP successfully addresses administrative challenges in the Faculty of Teacher Training and Education. This system contributes positively to data efficiency and accuracy, enhances the quality of academic services, and strengthens administrative transparency. Therefore, the application of web technology and PHP in the PPG Self-Reporting Information System can serve as a model for developing similar systems in other educational institutions.